2017
DOI: 10.1007/s00784-017-2271-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical survival of chair-side generated monolithic lithium disilicate crowns:10-year results

Abstract: The insertion of chair-side fabricated monolithic lithium disilicate crowns can be recommended for long-term use in the posterior region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 24 publications
2
74
3
3
Order By: Relevance
“…Survival rates between 93.4% and 100.0% have been reported in other investigations, but in these studies the follow‐up period was only 2 years . In one study with a 10 year follow‐up period, the survival rate was estimated to be 83.5% …”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Survival rates between 93.4% and 100.0% have been reported in other investigations, but in these studies the follow‐up period was only 2 years . In one study with a 10 year follow‐up period, the survival rate was estimated to be 83.5% …”
Section: Discussioncontrasting
confidence: 88%
“…The tooth vitality status and cement type did not affect the survival rate of crowns. Although previous studies reported the development of endodontic complications within a period of 2 years following crown placement, we did not observe any loss of vitality for the seven crowns placed on vital teeth over the 4‐year observation period. Neither location of tooth (maxilla or mandible) nor type of tooth (premolar or molar) affected the survival rate.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Lithium disilicate crowns showed favorable stability as crown material reported in a study that observed them up to 9 years . Rauch et al investigated the 10‐year performance of chairside monolithic lithium disilicate crowns and recommended these type of crowns be used in the posterior region in the long term . Teichmann et al also investigated lithium disilicate single crowns on teeth and implants and reported that the high potential of lithium disilicate as a reliable material, especially for single‐unit restorations .…”
Section: Introductionmentioning
confidence: 99%